2020
DOI: 10.1001/jamapsychiatry.2019.3867
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Connectivity Moderators of Antidepressant vs Placebo Treatment Response in Major Depressive Disorder

Abstract: IMPORTANCE Despite the widespread awareness of functional magnetic resonance imaging findings suggesting a role for cortical connectivity networks in treatment selection for major depressive disorder, its clinical utility remains limited. Recent methodological advances have revealed functional magnetic resonance imaging-like connectivity networks using electroencephalography (EEG), a tool more easily implemented in clinical practice. OBJECTIVE To determine whether EEG connectivity could reveal neural moderator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 81 publications
6
39
1
Order By: Relevance
“…Depending on the EEG characteristic and how it was MSE identified, 39-61% of our sample did not unambiguously show the same outcomes as their group, which is consistent with the idea that multiple response patterns to antidepressant treatment exist [50]. Taking alpha connectivity as an example, recent work shows that alpha connectivity profiles may differentially predict response to placebo versus antidepressant pharmacotherapy (setraline; [51]), highlighting the possibility that different alpha connectivity patterns may distinguish responders to different types of interventions. The decrease in alpha connectivity in treatment responders using group analyses in this and previous studies might thus only represent one of several response profiles that exist in patients with MDD.…”
Section: Discussionsupporting
confidence: 66%
“…Depending on the EEG characteristic and how it was MSE identified, 39-61% of our sample did not unambiguously show the same outcomes as their group, which is consistent with the idea that multiple response patterns to antidepressant treatment exist [50]. Taking alpha connectivity as an example, recent work shows that alpha connectivity profiles may differentially predict response to placebo versus antidepressant pharmacotherapy (setraline; [51]), highlighting the possibility that different alpha connectivity patterns may distinguish responders to different types of interventions. The decrease in alpha connectivity in treatment responders using group analyses in this and previous studies might thus only represent one of several response profiles that exist in patients with MDD.…”
Section: Discussionsupporting
confidence: 66%
“…For example, a large EEG study by Iseger et al 62 showed reduced alpha connectivity in male responders to a trial of antidepressant medication (Escitalopram, Sertraline, or Venlafaxine-XR). Pre-treatment alpha, beta, and gamma band connectivity has also been shown to moderate antidepressant (sertraline hydrochloride or placebo) treatment outcome in a recent large multi-centre study using a novel power envelope connectivity approach 63 ; while lower pre-treatment alpha-band connectivity has been observed in responders to ECT 64 . Although further work is needed to better elucidate the underlying mechanisms responsible for the observed connectivity changes in the present study, a recently proposed connectivity resetting hypothesis 9 might aid in partially explaining these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several potential resting state markers exist for predicting treatment outcome in major depression, such as frontal alpha asymmetry, 38 prefrontal theta cordance, 39 pretreatment rostral anterior cingulate theta activity, 40 antidepressant treatment response (ATR) index, 41 and EEG functional connectivity. 42 Other resting-state EEGbased biomarkers are promising for the identification of patients at risk of mild cognitive impairment due to Alzheimer's and Lewy body disease, 43 and for subtyping subjects with attention deficit hyperactivity disorder (ADHD). 44 EEG is also used to monitor the effects of certain drugs, like lithium carbonate used in the treatment of bipolar disorder.…”
Section: Clinical Data: What Is Used and Why Reported Main Electrophymentioning
confidence: 99%